Rapid integrated assessment of food safety and nutrition related to pork consumption of regular consumers and mothers with young children in Vietnam - Hung Nguyen-Viet; Sinh Dang-Xuan; Phuc Pham Duc; Roesel, Kristina; Nguyen Mai Huong; Toan Luu-Quoc; Pham Van Hung; Nguyen Thi Duong Nga; Lapar, Ma. Lucila; Unger, Fred; Häsler, Barbara; Grace, Delia (Elsevier, 2019)
Pork is the most common and widely consumed meat product in Vietnam. The study aimed to assess nutrition and food safety risks and opportunities associated with pork value chains in Vietnam. Twenty-nine focus group discussions (FGD) were conducted in Hung Yen and Nghe An provinces with 164 participants who were both regular pork consumers and mothers with young children. In each province, three districts were selected, and in each district we selected one commune. To assess the quality of pork, we took 30 swab samples of pig carcasses at slaughterhouses, 90 pork samples at slaughterhouses and markets and analysed all samples for total bacterial count (TBC), coliforms, water holding capacity and pH. The results showed that pork was the main livestock product consumed and women are responsible for buying and preparing food for daily meals. Pork was the main animal sourced food (ASF) for Vietnamese consumers, for 50–60% of ASF. There was little knowledge of zoonotic diseases. The findings suggest further studies to address consumers’ concern on chemical contamination. Most market pork samples were not within the allowable range of limits standards of Vietnam for bacterial contamination: 90% of samples were above the official permissible limit for TBC and 98% did not meet standards for coliforms. Fifty percent of samples had acceptable pH but only 5% had acceptable water holding capacity. There were no significant differences in pork quality between intensifying Hung Yen and traditional Nghe An provinces, although there was a tendency for samples from Hung Yen to have better compliance. This rapid assessment revealed considerable interest and knowledge on pork nutrition and safety and found some behavioural but few quality and safety differences between traditional and intensifying systems. This indicated marketed pork is of low quality and safety, and a lack of support to consumers in making good choices.